Prior surgical uterine evacuation of pregnancy and infertility: protocol for systematic review and meta-analysis. Issue 7 (2nd July 2020) - Tu, Pengcheng; Pei, Kaiyan
Abstract : Introduction: Prior surgical uterine evacuation is associated with an increased risk of infertility. However, findings are inconsistent, highlighting the need for a clear consensus on the effect of prior surgical uterine evacuation on the risk of infertility. Therefore, the aim of this systematic review and meta-analysis is to summarise the available evidence examining the association between prior surgical uterine evacuation and the risk of infertility. Methods and analysis: A systematic search of electronic databases (ie, PubMed, Scopus, ClinicalTrials.gov, EMBASE and ScienceDirect) will be conducted since their inception until October 2019 with no limit for language using a detailed prespecified search strategy. Both the authors will independently screen titles and abstracts and select full-text articles, perform data extraction and appraise the quality of included studies using a bias classification tool. Meta-analyses will be performed to calculate the overall pooled estimates using the generic inverse variance method. This systematic review and meta-analysis will follow the Preferred Reporting Items for Systematic Reviews and Meta Analyses (PRISMA) guidelines. Ethics and dissemination: Given that this is a protocol based on published data, there is no requirement for ethics approval. It is anticipated that the dissemination of results will be reported according to the PRISMA statement. The results will be published in peer-reviewed journals and presented at scientific conferences. PROSPERO registration number: CRD42019117266.